Community organization and armed group behaviour: Evidence from Colombia - Margarita Gáfaro; Ana María Ibá\~nez; Patricia Justino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper investigates how armed groups affect the organization of local communities during armed conflict in Colombia. We estimate the effect of communities' exposure to armed groups with an econometric specification that takes into account individual and municipality-year fixed effects and an instrumental variable approach that exploits variations in the presence of armed groups in rural communities induced by the peace negotiations with members of the Revolutionary Armed Forces of Colombia-People's Army. Our results show that the presence of armed groups in each community between survey rounds is accompanied by a reduction in the participation of individuals in local organizations in communities with a strong institutional set-up before the arrival of the armed group. We observe the opposite effect in communities with weaker pre-existing institutions. These results are consistent with a theoretical model in which armed groups capture local organizations for strategic war purposes.
Keywords: D74; H56; P37; 330; armed conflict; institutions; Colombia